138k views
3 votes
Simplify: 4- (3 1)2 - 6 2 4 2. Combine like terms: 7x3 2x - 5x2 6 x 9 3x3 12x2 3. Simplify: (2x5- ... Multiply: 3x2(4x3 - 2x2 7x - 4) 5. Evaluate: 6x2 ...

User SAVVY
by
5.1k points

1 Answer

4 votes

Answer:

The complete question is defined in the attached file please find it.

Explanation:

For question 1:


\to 4-(3+1)^2 - 6/ 2 +4 \\\\\to 4-(4)^2 - 6/ 2 +4\\\\\to 4-16 - 3 +4\\\\\to 4-19 +4\\\\\to 4-15\\\\\to -11

For question 2:


\to 7x^3 +2x -5x^2+6+ x+ 9+ 3x^3 +12x^2 \\\\\to 7x^3 +3x^3+12x^2 -5x^2+2x+x+9+6 \\\\\to 10x^3 +7x^2+3x+15 \\\\

For question 3:


\to (2x^5- 3x^2+4)-(x^5+2x^2+7)\\\\\to 2x^5- 3x^2+4-x^5-2x^2-7\\\\\to x^5- 5x^2-3\\\\

For question 4:


\to 3x^2(4x^3- 2x^2+7x -4) \\\\\to 12x^5- 6x^4+21x^3 -12x^2 \\\\

For question 5:


\to 6x^2+9x-7 \ \ \text{when} \ \ x=2\\\\\to 6(2)^2+9(2)-7 \\\\\to 6(4)+9(2)-7 \\\\\to 24+18-7 \\\\\to 24+11 \\\\\to 35

Simplify: 4- (3 1)2 - 6 2 4 2. Combine like terms: 7x3 2x - 5x2 6 x 9 3x3 12x2 3. Simplify-example-1
User Vikram Gulia
by
5.0k points